2013
DOI: 10.1186/1471-2164-14-462
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation is a conserved epigenetic feature found throughout the phylum Platyhelminthes

Abstract: BackgroundThe phylum Platyhelminthes (flatworms) contains an important group of bilaterian organisms responsible for many debilitating and chronic infectious diseases of human and animal populations inhabiting the planet today. In addition to their biomedical and veterinary relevance, some platyhelminths are also frequently used models for understanding tissue regeneration and stem cell biology. Therefore, the molecular (genetic and epigenetic) characteristics that underlie trophic specialism, pathogenicity or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 64 publications
3
49
0
Order By: Relevance
“…T. solium cysticerci have developed diverse mechanisms to protect themselves from host immune attack [26], among which epigenetics may play an important role in gene regulation related to parasitism [24]. Recently, Geyer et al found that essential DNA methylation machinery components, such as DNMT2 and MBD, are well conserved throughout the Platyhelminthes [4, 27]. Invertebrate DNMT2s are believed to retain strong DNA methyltransferase activity [28], which is different from vertebrate DNMT2s, which are considered tRNA methyltransferases [29].…”
Section: Discussionmentioning
confidence: 99%
“…T. solium cysticerci have developed diverse mechanisms to protect themselves from host immune attack [26], among which epigenetics may play an important role in gene regulation related to parasitism [24]. Recently, Geyer et al found that essential DNA methylation machinery components, such as DNMT2 and MBD, are well conserved throughout the Platyhelminthes [4, 27]. Invertebrate DNMT2s are believed to retain strong DNA methyltransferase activity [28], which is different from vertebrate DNMT2s, which are considered tRNA methyltransferases [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, DNMT2-only or DNMT-free organisms contradicted the widely accepted role of DNA methylation in eukaryotes (Jeltsch, 2010;Raddatz et al 2013). 1; Geyer et al 2013). 1; Geyer et al 2013).…”
Section: Methyltransferase Activity Of Rcsdnmt2 Orfmentioning
confidence: 99%
“…Recently, cytosine methylation was found to be a conserved epigenetic feature throughout the phylum Platyhelminthes, including Schistosoma haematobium, Schistosoma japonicum , and S. mansoni (Geyer et al, 2013). In addition to cytosine methylation, the arginine methyltransferase PRMT1 homolog was identified in S. mansoni and S. japonicum (Mansure et al, 2005; Diao et al, 2014).…”
Section: Epigenetic Studies In Schistosomes: What Is Known?mentioning
confidence: 99%